FISH AND VEGETABLE CULTIVATION AT HOME: Alternative Fulfillment of Living Needs - Deni Saputra; Yusnani Yusnani; Aan Sanawiyah (Jurnal PKM Manajemen Bisnis, 2021)
Life requires the ability to survive, one of which is the cultivation of fish and vegetables. Maybe for some people, this is considered not very important. However, this small thing in difficult circumstances such as a pandemic, can be an option in maintaining survival. The harsh dynamics of life, guide each of us, can maximize our potential, including fish farming and farming. This service activity is carried out as a form of knowledge sharing and training to the community, that there are many things that can be done to meet the economic needs of the family. This activity was held in Pamulang District (South Tangerang) for three days. The activity method is carried out by means of discussion and practice. What can be stated from the results of this service activity is that training in fish and vegetable cultivation has received a positive response from the community. Especially during the pandemic, participants realized that there was a lot of free time that needed to be filled with useful activities, so this training opened public knowledge and awareness that fish and vegetable farming can be done at home and become an alternative to fulfill their daily needs.